Nosocomial Infections-An Overview of Prophylactic Approaches to Control VAP - Charan, Ajay; Thomas, Lita Susan; Bambal, Vaishali; Kenchappa, Vanaja; Jose, Anju (International Journal of Pharmaceutical Investigation, 2025)
Ventilator-Associated Pneumonia (VAP) is a prevalent and serious hospital-acquired infection occurring in critically ill patients who have been mechanically ventilated for over 48 hr. It is primarily caused by Gram-negative pathogens such as Pseudomonas aeruginosa, Acinetobacter baumannii, and members of the Enterobacteriaceae family. Reported global incidence rates range from 8.9 to 46 cases per 1,000 ventilator days, reflecting variability in ICU practices and patient populations. VAP is a major contributor to antibiotic overuse in intensive care units, fuelling the rise of Multidrug-Resistant (MDR) organisms and complicating patient management. Its pathogenesis involves the disruption of natural airway defenses by endotracheal intubation, which promotes bacterial colonization and micro aspiration of contaminated secretions. Key risk factors include mechanical ventilation, extended ICU stays, and underlying conditions such as Chronic Obstructive Pulmonary Disease (COPD) and cystic fibrosis. Preventive strategies emphasize rigorous infection control, such as maintaining appropriate endotracheal cuff pressure, routine oral hygiene, and timely ventilator circuit maintenance. While prophylactic antibiotics have been used, their application must be judicious to prevent the emergence of resistant pathogens. Emerging biomarkers-including soluble Triggering Receptor Expressed on Myeloid cells-1 (sTREM-1), Procalcitonin (PCT), and C-Reactive Protein (CRP)-are under investigation for their potential to enhance diagnostic accuracy and guide antimicrobial stewardship.
Keywords: Ventilator-Associated Pneumonia (VAP); Prophylaxis; Infection control; Formulations; Biomarkers and antimicrobial resistance